Tubular Dysfunction and Ruptured Ureter in a Child with Menkes Syndrome - Wun Fung Hui; Kam Lun Hon; Alexander K. C. Leung; Kristine Kit Yi Pang; Michael Wai Yip Leung (Hindawi Limited, 2021)
Children with Menkes disease may develop various urological and renal problems that evolve as the disease progresses. A 4-year-old boy with Menkes disease had multiple bladder diverticula and a history of recurrent urinary tract infection caused by urea-splitting organisms. The child developed urosepsis and right pyelonephritis. Subsequent investigations revealed multiple right renal stones and a ruptured right ureter. The child also developed hypokalemia, hypophosphatemia, and normal anion gap metabolic acidosis that required electrolyte and potassium citrate supplement. Further assessment revealed renal tubular dysfunction. Our case suggests that regular imaging surveillance, monitoring of renal function and electrolyte profile, and tubular function assessment should be considered in children with Menkes disease.